2018
DOI: 10.1186/s12920-018-0331-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel candidate genes important for asthma and hypertension comorbidity revealed from associative gene networks

Abstract: Background: Hypertension and bronchial asthma are a major issue for people's health. As of 2014, approximately one billion adults, or~22% of the world population, have had hypertension. As of 2011, 235-330 million people globally have been affected by asthma and approximately 250,000-345,000 people have died each year from the disease. The development of the effective treatment therapies against these diseases is complicated by their comorbidity features. This is often a major problem in diagnosis and their tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 163 publications
(175 reference statements)
1
39
0
8
Order By: Relevance
“…In large twin populations from Scandinavia, genetic traits for asthma overlapped with those from different affective disorders such as major depression disorder, primary anxiety disorder, and most of all, neuroticism [16]. Using sophisticated bioinformatics tools, also an overlap between gene networks contributing to asthma and hypertension based on genetic databases and bioinformatic ranking algorithms was identified [17]. The genes most likely in the center of the asthma and hypertension interaction were IL10, TLR4, and CAT, suggesting that mechanisms of adaptive and innate immunity are shared in the development of both diseases.…”
Section: Genetic Pleiotrophy For Comorbidities With Asthma and Allergymentioning
confidence: 99%
“…In large twin populations from Scandinavia, genetic traits for asthma overlapped with those from different affective disorders such as major depression disorder, primary anxiety disorder, and most of all, neuroticism [16]. Using sophisticated bioinformatics tools, also an overlap between gene networks contributing to asthma and hypertension based on genetic databases and bioinformatic ranking algorithms was identified [17]. The genes most likely in the center of the asthma and hypertension interaction were IL10, TLR4, and CAT, suggesting that mechanisms of adaptive and innate immunity are shared in the development of both diseases.…”
Section: Genetic Pleiotrophy For Comorbidities With Asthma and Allergymentioning
confidence: 99%
“…GenCoNet is meant to be a qualitative resource that facilitates researchers access the relevant information. Our study [1] showed that the application of methods of reconstruction and analysis of gene networks is a productive tool to rank candidate genes by their importance to complex diseases (e.g. asthma and hypertension).…”
mentioning
confidence: 93%
“…Поддерживая эти наблюдения, функциональный анализ показал, что IL-17A и IL-17F способны стимулировать бронхиальные фибробласты, эпителиальные клетки и клетки гладкой мускулатуры и вызывать экспрессию различных цитокинов и хемокинов, включая IL-8, IL-6, IL-11 и CXCL1, которые важны для гранулопоэза и нейтрофилов [15]. Способность IL-17A и IL-17F индуцировать миграцию нейтрофилов предполагает, что они участвуют в патогенезе тяжелой формы БА, основной характеристикой которой является нейтрофильное воспаление в дыхательных путях [14,15] Генетические исследования полиморфных генов могут служить способом, помогающим продемонстрировать связи между определенными белками и БА, характеризующиеся взаимодействием нескольких генов в разных хромосомах [3,14,17,18]. Гены, кодирующие семейство IL-17, расположены на 6q12 хромосоме, при множественном сканировании генома показано, что это геномная область, связанная с определенными фенотипами БА [19].…”
Section: Introductionunclassified